Development of The Theory of Planned Behavior with Sharia Compliance as a Moderating Variable - Sikumbang, Purnama Raya; Siregar, Ibrahim; Cahyani, Utari Evy (Al-Mashrof: Islamic Banking and Finance, 2025)
contributors to Indonesia’s economic growth, yet they continue to encounter significant barriers in accessing formal financial services. To address this gap, Pegadaian, a non-bank financial institution, offers Sharia KUR as an alternative financing scheme for unbankable MSMEs. This study investigates customer behavior in adopting Sharia KUR using the Theory of Planned Behavior (TPB) framework and evaluates the moderating role of Sharia compliance. Employing a quantitative survey method, data were collected from 356 respondents at Pegadaian UPC Natal Barumun, and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) through WarpPLS 7.0. Empirical findings reveal that attitude (β=0.545; p<0.001) and perceived behavioral control (β=0.107; p=0.021) exert positive and significant effects on intention to use Sharia KUR, whereas subjective norms (β=0.078; p=0.068) show no significant influence. Intention itself strongly predicts financing behavior (β=0.550; p<0.001). In contrast, Sharia compliance does not significantly moderate the intention–behavior relationship (β=0.071; p=0.088). These results emphasize that internal factors, particularly perceived benefits, ease of access, outweigh social pressures in shaping customer behavior. Practically, study underscores the need to strengthen Islamic financial literacy, enhance product transparency, and develop continuous education strategies to foster trust and encourage greater utilization of Sharia-based financing. Keywords: MSMEs, KUR Syariah, TPB, Shariah Compliance, Financing Behavior.